VD_FINDINFO HC / 2014 / 403 vom 26. Mai 2014 - VD Tribunal cantonal (2014)
PROTECTION DE L'UNION CONJUGALE, TRANSACTION JUDICIAIRE, OBLIGATION D'ENTRETIEN | 105 al. 1 CPC (CH), 109 al. 1 CPC (CH), 241 al. 2 CPC (CH), 241 al. 3 CPC (CH), 65 al. 2 TFJC (2010), 67 al. 2 TFJC (2010)